Problematika Pelaksanaan Putusan Mahkamah Agung dalam Pengujian Peraturan Perundang-Undangan di Bawah Undang-Undang: Studi Analisis Putusan Nomor 57/P/HUM/2019 - Sahiddin, Moh Farid Insan; Ichlas, Rudy Iskandar; Jambak, Fahmi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The implementation of Supreme Court decisions in reviewing regulations below statutes constitutes a crucial mechanism to uphold the rule of law and maintain normative hierarchy. However, in practice, the enforcement of material judicial review decisions frequently encounters structural and normative obstacles. This study aims to analyze the problems surrounding the implementation of Supreme Court Decision Number 57/P/HUM/2019 and its implications for legal certainty and the effectiveness of judicial review in Indonesia. This research employs a normative juridical method using statutory and case approaches. The findings reveal that weak execution mechanisms, absence of sanctions for non-compliance, and the dualism of judicial review authority between the Supreme Court and the Constitutional Court contribute to the ineffectiveness of such decisions. Strengthening the binding force of Supreme Court rulings requires harmonization of the judicial review system and the establishment of supervisory enforcement mechanisms.